Wigner rotations and an apparent paradox in relativistic quantum information - Saldanha, P; Vedral, V (2013)
It is shown that a general model for particle detection in combination with a linear application of the Wigner rotations, which correspond to momentum-dependent changes of the particle spin under Lorentz transformations, to the state of a massive relativistic particle in a superposition of two counterpropagating momentum states leads to a paradox. The paradox entails the instantaneous transmission of information between two spatially separated parties. A solution to the paradox is given when the physical construction of the corresponding state is taken into account, suggesting that we cannot in general linearly apply the Wigner rotations to a quantum state without considering the appropriate physical interpretation. © 2013 American Physical Society.